2020
DOI: 10.20944/preprints202011.0060.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trajectories of Cotton Fiber Initiation: A Regulatory Perspective

Abstract: The epidermal cells on the surface of the cotton ovules undergo differentiation to produce fibers, which are single-celled hair-like protrusions resembling the plant trichomes. The initiation of these unicellular fibers from the cotton ovule surface is a complex and tightly regulated process. The initiation step is the cell fate-determining stage, which leads to the commitment of cells that eventually developed into fibers, thus becomes the most crucial phase in fiber development. The in-depth knowledge of mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 109 publications
(204 reference statements)
0
4
0
Order By: Relevance
“…, initiation, elongation, secondary cell wall biosynthesis, and maturation. The fate of ovule epidermal cells is committed before and/or on the day of anthesis, which is coordinated by different regulation machinery ( Qin and Zhu, 2011 ; Zhang et al, 2017 ; Prakash et al, 2020 ; Tian and Zhang, 2021 ). Thus, we named this stage as a fiber commitment stage, which ultimately decided the total fiber yield ( Wang L. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…, initiation, elongation, secondary cell wall biosynthesis, and maturation. The fate of ovule epidermal cells is committed before and/or on the day of anthesis, which is coordinated by different regulation machinery ( Qin and Zhu, 2011 ; Zhang et al, 2017 ; Prakash et al, 2020 ; Tian and Zhang, 2021 ). Thus, we named this stage as a fiber commitment stage, which ultimately decided the total fiber yield ( Wang L. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, all these phytohormones positively regulating the commitment of fiber cells under the effect of different GhCYPs (Fig. 5A-5D) [47]. Contrastingly, GhCYP707 modulates the Abscisic acid concentration that negatively regulates the cotton fiber initiation at -3 to 3 DPA fiber developmental stages (Supplementary Dataset 7) [48,49].…”
Section: Discussionmentioning
confidence: 87%
“…The MYB transcription factor GhCPC is homologous to Arabidopsis CPC and negatively regulates cotton fiber elongation. Transgenic evidence suggests that overexpression of GhCPC results in a delay in fiber initiation and a reduction in fiber length ( Prakash et al, 2020 ). A yeast two-hybrid analysis showed that GhCPC can interact with the bHLH-type protein GhMYC1, and GhMYC1 can also interact with GhTTG1 and GhTTG4 .…”
Section: Molecular Mechanisms Of Unicellular Trichome Developmentmentioning
confidence: 99%
“…The expression of VACUOLAR INVERTASE ( VIN ) is necessary for cotton fiber initiation, and RNAi-mediated inhibition of GhVIN1 leads to a significant decrease in VIN activity, thereby forming a fiber-free seed phenotype in a dose-dependent manner ( Wang et al, 2014 ). GhVIN1 -mediated hexose signaling acts upstream of GhMYB25-like , GhMYB25 , and GhMYB109 transcription factors ( Prakash et al, 2020 ).…”
Section: Molecular Mechanisms Of Unicellular Trichome Developmentmentioning
confidence: 99%